Monitoring of Trough Plasma Ganciclovir Levels and Peripheral Blood Cytomegalovirus (CMV)-Specific CD8(+) T Cells To Predict CMV DNAemia Clearance in Preemptively Treated Allogeneic Stem Cell Transplant Recipients - Giménez, Estela (American Society for Microbiology, 2014)
It is uncertain whether monitoring plasma ganciclovir (GCV) levels is useful in predicting cytomegalovirus (CMV) DNAemia clearance in preemptively treated allogeneic stem cell transplant recipients. In this observational study, including 13 episodes of CMV DNAemia treated with intravenous (i.v.) GCV or oral valganciclovir, we showed that monitoring trough plasma GCV levels does not reliably predict response to therapy. Rather, immunological monitoring (pp65 and immediate-early [IE]-1-specific gamma interferon [IFN-γ]-producing CD8(+) T cells) appeared to perform better for this purpose.